Validation of the Chinese version of public attitudes toward epilepsy scale in Mainland China - Yue, Z.; Ma, C.; Lim, K.S.; Xiao, B.; Wu, Q.; Shu, Y.; Yue, Z.; Wang, Y.; Feng, L. (Elsevier, 2017)
Purpose Epilepsy is a significant yet seriously underappreciated public health issue in Mainland China. The stigma and discrimination toward people with epilepsy (PWE) and their families are especially severe in China based on cultural misconceptions which cause tremendous psychological, economic and social burdens. It is imperative to formulate a targeted public intervention to eliminate knowledge gaps and correct these misconceptions of epilepsy. However, to date, the essential tools that may drive such an intervention by measuring the public perspective on PWEs is lacking in China. The goal of this study is to test the reliability and validity of a Simplified Chinese version of the “Public Attitude Toward Epilepsy” scale (PATE) in Mainland China which can be used to understand the content and identify the possible sources of stigma to better inform the design and focus of future stigma reduction interventions. Methods The standard procedure of cross-cultural adaptation was used in the translation process. Subjects from different economic and social backgrounds were enrolled by convenience sampling in central China. Exploratory factor analysis and confirmatory factor analysis were used to check the underlying factor structure of the items. Furthermore, Cronbach's alpha was utilized to assess internal consistency. Results 199 respondents were included in the final analysis. Content validity of this Chinese PATE was assessed to be adequate for assessing public attitudes toward epilepsy among the mainland Chinese. Two factors were extracted from the data by exploratory factor analysis; confirmatory factor analysis further confirmed good consistency of theoretical constructs between the original Public Attitudes Toward Epilepsy scale and our Chinese PATE. Our Chinese PATE presented excellent internal consistency (α = 0.853–0.909). Conclusion This version of the Chinese PATE showed acceptable psychometric properties, indicating that it can be implemented in surveying public attitudes toward epilepsy in Mainland China.